Technological Infrastructure In Teaching-Learning Processes In Educational Institutions: A Systematic Review - Navarro, Rafael Cecilio (2025)
The COVID-19 pandemic accelerated the adoption of virtual and hybrid teaching methods, leading to substantial changes in educational approaches. This study focused on evaluating the effect of mediating technologies on post-pandemic educational processes, emphasizing their essential role in enhancing interaction and cooperation between teachers and students. Although their relevance is evident, challenges persist in terms of access, quality, and evaluation of technological educational initiatives. To address these challenges, a comprehensive literature review was conducted, examining 26 international academic studies published in the last five years. The findings indicate that mediating technologies positively influence motivation, student retention, and self-directed learning, especially in higher education and language teaching. However, the effects vary depending on the context. It is recommended to implement a technological strategy in the classroom that enhances learning and supports holistic education, highlighting the importance of developing comprehensive programs for planning, execution, and evaluation of educational technologies before applying these findings in specific contexts like Colombia.